Technostress and Emotional Intelligence: A Bibliometric Analysis Using Dimensions Database - Subedi, Manoj; Prajapati, Nisha (Journal of Emerging Management Studies, 2025)
Purpose – The objective of this study is to apply bibliometric analysis to provide a thorough overview of the research landscape surrounding technostress and emotional intelligence. By examining the literature, the analysis aims to identify key trends, and areas of growing interest in this field. Design/methodology/approach – This study used bibliometric analysis to explore the relationship between technostress and emotional intelligence from the study 2015 to 2025, applying the Dimensions database and VOSviewer software. The research analyzed 700 open-access articles to map key trends, influential authors, and emerging areas in this field. It used citation network analysis, co-authorship analysis, and trend analysis to examine collaboration patterns and the growth of research over time. Findings – The findings of the study showed a steady increase in research on technostress and emotional intelligence from 2015 to 2025, with a sharp rise post-2020, likely influenced by the COVID-19 pandemic. Key contributors to the field include foundational studies on technological addiction and mental health, with later research building on these topics to address issues like workplace burnout and remote work. The co-authorship network highlighted strong international collaboration, with notable clusters in Western countries, East Asia, and the Middle East, suggesting a global interest in these topics. The citation network analysis identified influential studies and emphasized the ongoing relevance of early research, while the bibliographic coupling revealed a growing focus on workplace stress, digital technology’s impact, and emotional intelligence in managing technostress. Conclusion – The bibliometric analysis advocates a significant shift in academic focus towards technostress and emotional intelligence, particularly after 2020, driven by digital work transformation and the COVID-19 pandemic. The increase in publications reflects growing recognition of the psychological impact of technology on mental health, especially in remote work, with EI emerging as a key tool for managing technostress. Originality/value – This research adds new insights to the field by examining the interconnections between emotional intelligence, technostress in the context of digital transformation and remote work.